SITUATIONS, FACTORS, EFFECTS OF LIFESTYLE AND THEIR EFFECTIVE SOLUTIONS CAUSING STRESS AND DEPRESSION (Conference Zone, 2022)
This article analyzes stressful situations in human life and their impact and offers solutions based on these problems. real-life examples have been cited as the main problem of people in the modern world today is stress